The effects of the Chilean school accountability system on teacher turnover - Gregory Elacqua; Diana Hincapié; Matías Martínez (Inter-American Development Bank (IDB), 2019)
This paper estimates the effects of school accountability on year-to-year teacher mobility in Chile. An accountability program was introduced between 2012 and 2015, which established sanctions for persistently low-performing schools, including the threat of closure if they failed to improve their academic outcomes after four years. Since the low-performance ranking was based on the school's relative position on a set of variables and their corresponding thresholds, we use a Multivariate Regression Discontinuity Design to evaluate the impact of the policy on teacher mobility. Our results indicate that teachers are more likely to leave schools that are labeled as low performing. This effect appears to be relevant only when teachers can move to other schools, as we did not find any effect on the likelihood of teachers leaving the school system. The evidence suggests that the effect on mobility is more pronounced for teachers with less working experience, who teach in two or more schools, were hired with temporary contracts, and achieved lower scores on their college admission tests. Even though mobility appears to have increased among less effective teachers, schools are not hiring new teachers to replace them.
Keywords: I28; J18; I24; J63; 330; School accountability; Teacher mobility; Multivariate regression discontinuity